Management of Recurrent Acute Rhinosinusitis: A Systematic Review. Issue 6 (November 2021) - Saltagi, Mohamad Z.; Comer, Brett T.; Hughes, Samuel; Ting, Jonathan Y.; Higgins, Thomas S.
Background Objective Study Design: RARS is a challenging clinical problem that impacts many patients. This article seeks to systematically review the literature on RARS management. Methods: Cochrane, PubMed, EMBASE, and other databases were queried for articles related to RARS dating from 1990 to present, according to PRISMA guidelines. Inclusion criteria included articles specifically addressing RARS management; studies with 3 or more patients; and articles in English. Results: A total of 1022 titles/abstracts potentially related to RARS were identified. Of these, sixty-nine full texts were selected for review, and 10 met inclusion criteria (five with level 4 evidence, four with level 3 evidence, one with level 2 evidence). The studies included a total of 890 patients (Age range 5.8 to 53.5 years), with follow up ranging from 1 to 19 months. Endpoints were primarily based on symptomatic improvement, although some articles also reported post-treatment endoscopic and radiographic findings. Management options included medical therapy (intranasal steroids, antibiotics, nasal saline irrigations, N-acetylcysteine, allergy treatment, and decongestants), balloon sinus dilation (BSD), and endoscopic sinus surgery (ESS). Surgical patients (BSD and ESS) had a trend towards greater symptom control than medically-treated patients, but meta-analysis was not possible. Conclusion: Despite increasing interest in the treatment of RARS, there remains a lack of consensus regarding optimal management. The literature thus far, largely based on expert opinion, suggests that surgical management, either through balloon sinus dilation or endoscopic sinus surgery, may be helpful in improving symptoms and quality of life in those who do not respond to initial trials of medical management.